ASPIRATIONS AND IDENTITIES: PROXENIA AT OROPOS DURING THE FOURTH TO SECOND CENTURIES BC. (December 2015) - WILDING, ALEXANDRA
Abstract : Inscribed grants of proxenia were more than just stone copies of a community's diplomatic and honorific transactions. The paper presented here, which focuses upon the widespread inscription of proxeny decrees at Oropos during the fourth to second centuries BC, argues that the documentation of such awards enabled clear public expression of the multifaceted aspirations and identities a community wished to enunciate; in the case of the Oropian dēmos, it articulated both polis identity and its place within the Boiotian confederacy of the Hellenistic period. The city‐stateof Oropos is often perceived as a vulnerable territory with severely limited independence, but this paper, by assessing the features and epigraphical practices of those 275 extant Oropian grants of proxeny status, offers fresh insight into its community's social and political expressions, as well as their ambitions in the late Classical and Hellenistic periods.